2015
DOI: 10.2967/jnumed.115.154815
|View full text |Cite
|
Sign up to set email alerts
|

Semiquantitative 123I-Metaiodobenzylguanidine Scintigraphy to Distinguish Pheochromocytoma and Paraganglioma from Physiologic Adrenal Uptake and Its Correlation with Genotype-Dependent Expression of Catecholamine Transporters

Abstract: 123 I-metaiodobenzylguanidine ( 123 I-MIBG) scintigraphy plays an important role in the diagnostic evaluation of patients with pheochromocytoma and paraganglioma (PPGL). 123 I-MIBG targets cell membrane and vesicular catecholamine transporters of chromaffin cells and facilitates localization of the primary tumor and metastatic lesions. Its specificity for the diagnosis of adrenomedullary chromaffin cell tumors can be jeopardized by physiologic uptake by the normal adrenal medulla. The aim of this study was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…MIBG imaging has been well established as a localizing tool and a functional marker of catecholamine secreting tissue, with a high sensitivity range (83%-100%) and a high specificity (95-100%) (24,25,30). MIBG demonstrated a high diagnostic accuracy in four patients, who had pheochromocytomas confirmed by histopathology and were positive on the MIBG scan.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…MIBG imaging has been well established as a localizing tool and a functional marker of catecholamine secreting tissue, with a high sensitivity range (83%-100%) and a high specificity (95-100%) (24,25,30). MIBG demonstrated a high diagnostic accuracy in four patients, who had pheochromocytomas confirmed by histopathology and were positive on the MIBG scan.…”
Section: Discussionmentioning
confidence: 98%
“…Conversely, due to its high sensitivity 99m Tc-HYNIC-TOC scintigraphy can be considered as the first choice scintigraphic imaging technique in paragangliomas. (24,25,30,31,39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, subjects with VHL have lower VMATs expression in chromaffin tissue, possibly hampering the use of MIBG as an effective functional imaging agent ( 29 , 30 ). Additionally, 123 I-MIBG uptake was not correlated with either hNET or VMAT (VMAT-1 in particular) expression in a series of 62 patients with PHEOs/PGLs, including two patients with VHL ( 31 ). In a comparison between VHL patients and SHDB patients, a study found that MIBG was overall positive in 11/12 VHL patients but was falsely negative in 3/5 VHL patients with synchronous bilateral adrenal PHEOs ( 32 ).…”
Section: Functional Imaging In Patients With Vhlmentioning
confidence: 92%
“…9 The role of heparin lies in its ability to activate lipoprotein lipase which leads to an increase in the supply of fatty acids. 10 18 FDG PET images are subsequently interpreted using a variety of methods, including visual review of the 18 FDG images, a semiquantitative scale and standardized uptake values (SUVs).…”
Section: The Role Of Preparation Prior To Pet Imagingmentioning
confidence: 99%